Targeting the Heme-Heme Oxygenase System to Prevent Severe Complications Following COVID-19 Infections - Frank A. D. T. G. Wagener; Peter Pickkers; Stephen J. Peterson; Stephan Immenschuh; Nader G. Abraham (MDPI AG, 2020)
SARS-CoV-2 is causing a pandemic resulting in high morbidity and mortality. COVID-19 patients suffering from acute respiratory distress syndrome (ARDS) are often critically ill and show lung injury and hemolysis. Heme is a prosthetic moiety crucial for the function of a wide variety of heme-proteins, including hemoglobin and cytochromes. However, injury-derived free heme promotes adhesion molecule expression, leukocyte recruitment, vascular permeabilization, platelet activation, complement activation, thrombosis, and fibrosis. Heme can be degraded by the anti-inflammatory enzyme heme oxygenase (HO) generating biliverdin/bilirubin, iron/ferritin, and carbon monoxide. We therefore postulate that free heme contributes to many of the inflammatory phenomena witnessed in critically ill COVID-19 patients, whilst induction of HO-1 or harnessing heme may provide protection. HO-activity not only degrades injurious heme, but its effector molecules possess also potent salutary anti-oxidative and anti-inflammatory properties. Until a vaccine against SARS-CoV-2 becomes available, we need to explore novel strategies to attenuate the pro-inflammatory, pro-thrombotic, and pro-fibrotic consequences of SARS-CoV-2 leading to morbidity and mortality. The heme-HO system represents an interesting target for novel "proof of concept" studies in the context of COVID-19.